The Influence of Shortening on Clinical Outcome in Healed Displaced Midshaft Clavicular Fractures After Nonoperative Treatment. (19th July 2017) - Goudie, E.B.; Clement, N.D.; Murray, I.R.; Lawrence, C.R.; Wilson, M.; Brooksbank, A.J.; Robinson, C.M.
Abstract : Background: We aimed to evaluate the effect of clavicular shortening, measured with 3-dimensional computed tomography (3DCT), on functional outcomes and satisfaction in patients with healed displaced midshaft clavicular fractures up to 1 year following injury. Methods: The data used in this study were collected as part of a multicenter, prospective randomized controlled trial of open reduction and plate fixation compared with nonoperative treatment for acute, displaced midshaft clavicular factures. Patients who were randomized to nonoperative treatment and had healed by 1 year were included in the present study. Clavicular shortening relative to the uninjured, contralateral clavicle was measured on 3DCT. Outcome analysis was conducted at 6 weeks, 3 months, 6 months, and 1 year following injury and included the Disabilities of the Arm, Shoulder and Hand (DASH), Constant, and Short Form-12 (SF-12) scores and patient satisfaction. Results: In the original trial, 105 patients were randomized to nonoperative treatment. Thirteen patients were lost to follow-up, leaving 92 patients, and an additional 16 (17%) developed nonunion and were excluded from the present study. Of the remaining 76 patients, 48 who had a 3DCT scan that included the whole length of both clavicles were included in the present study. The shortening of the injured clavicles, relative to the contralateral side, was a mean (and standard deviation) of 11.3 ± 7.6 mm, with a mean proportional shortening of 8%. Proportional shortening did not significantly correlate with the DASH (p ≥ 0.42), Constant (p ≥ 0.32), or SF-12 (p ≥ 0.08) scores at any point during follow-up. There was no significant difference in the mean DASH or Constant scores at any follow-up time point when the cutoff for shortening was defined as 1 cm (p ≥ 0.11) or as 2 cm (p ≥ 0.35). There was no significant difference in clavicular shortening between satisfied and unsatisfied patients (p ≥ 0.49). Conclusions: The present study demonstrated no association between shortening and functional outcome or satisfaction in patients with healed displaced midshaft clavicular fractures up to 1 year following injury. Level of Evidence: TherapeuticLevel IV . See Instructions for Authors for a complete description of levels of evidence.